Limitations of Using IL-17A and IFN-γ-Induced Protein 10 to Detect Bovine Tuberculosis - Xin, Ting; Gao, Xintao; Yang, Hongjun; Li, Pingjun; Liang, Qianqian; Hou, Shaohua; Sui, Xiukun; Guo, Xiaoyu; Yuan, Weifeng; Zhu, Hongfei; Ding, Jiabo; Jia, Hong (Frontiers in Veterinary Science, 2018)
Bovine tuberculosis (bTB) is primarily caused by infection with Mycobacterium bovis, which belongs to the Mycobacterium tuberculosis complex (MTC). The airborne route is considered the most common for transmission of M. bovis, and more than 15% of cattle with bTB shed the mycobacterium, which can be detect by nested PCR to amplify mycobacterial mpb70 from a nasal swab from a cow. To screen for cytokines fostering early and accurate detection of bTB, peripheral blood mononuclear cells (PBMCs) were isolated from naturally M. bovis-infected, experimentally M. bovis 68002-infected, and uninfected cattle, then these cells were stimulated by PPD-B, CFP-10-ESAT-6 (CE), or phosphate-buffered saline (PBS) for 6 h. The levels of IFN-γ, IP-10, IL-6, IL-12, IL-17A, and TNF-α mRNA were measured using real-time PCR. To explore the cytokines associated with different periods of M. bovis infection, cattle were divided into three groups: PCR-positive (PCR-P), PCR-negative (PCR-N), and uninfected using the tuberculin skin test (TST), CFP-10/ESAT-6/TB10.4 protein cocktail-based skin test, interferon gamma (IFN-γ) release assay (IGRA), CFP-10/ESAT-6 (CE)-based IGRA, and nested PCR. The expression of IP-10, IL-17A, and IFN-γ proteins induced by PPD-B, CE, or PBS was detected by ELISA. The results showed that levels of PPD-B-stimulated IL-17A and IP-10 (mRNA and protein), and CE-induced IP-10 (mRNA and protein) were significantly higher in cattle naturally or experimentally infected with M. bovis than in those that were uninfected. The levels of PPD-B- or CE-induced IL-17A and IP-10 (protein) could be used to differentiate M. bovis-infected calves from uninfected ones for 6 to 30 weeks post-infection, whereas PPD-B- and CE-induced IP-10 and IL-17A mRNA expression could be used to differentiate M. bovis-infected calves from uninfected ones between 6 and 58 weeks post-infection. However, CE-induced IL-17A (protein) was not a reliable indicator of M. bovis infection in cattle that were confirmed positive for infection by nested PCR. Furthermore, the levels of PPD-B- or CE-induced IP-10 and IL-17A protein were lower than IFN-γ in M. bovis-infected cattle. Therefore, IL-17A and IP-10 protein are not suitable biomarkers for bTB. Antigen-induced IP-10 mRNA should be analyzed further for their potential to be used in the diagnosis of bTB.